A Flipped Classroom Design for a Practical-Oriented Mechanical Engineering Curriculum Titled Technical English - Fang, Ziqiang; Liu, Yuhang (Education Insights, 2026)
The salient features of the Mechanical Engineering curriculum titled Technical English is that the professional terms and phrases are characterized by strong professionalism and a narrow application scope. The knowledge points covered in this curriculum are closely related to branches including Materials Science, Mechanics, and Graphics. During the long-term teaching practice, it was found that the current instructional process is challenged by the three problems: (1) The teaching content is not oriented towards engineering practice; (2) The knowledge system and modularization in instruction are insufficient; (3) A low level classroom participation are among the students. Aiming at the above problems, the knowledge of technical practice is introduced into the teaching process of Technical English. Through adopting the flipped classroom teaching method, students' role can be shifted from passive listeners to engaged learners in the classroom. Taking the cross-fusion teaching design between the two curriculum of Technical English and Production Line Course Design, a case study in practice-embedded Technical English instruction for Mechanical Engineering is designed and implemented.